Discovery, Characterization, and Pharmaceutical Applications of Two Loratadine–Oxalic Acid Cocrystals - Zhengxuan Liang; Hongbo Chen; Chenguang Wang; Changquan Calvin Sun (Crystals, 2020)
Loratadine (Lor) is an antihistamine drug commonly used to relieve the symptoms of allergy. It has high permeability but low solubility under physiological conditions. To overcome the problem of low solubility, we synthesized and characterized two Loratadine multi-component crystalline phases with oxalic acid (Oxa), i.e., a 1:1 Lor-Oxa conjugate acid-base (CAB) cocrystal (Lor-Oxa CAB) and a 2:1 Lor-Oxa cocrystal monohydrate (Lor-Oxa hydrate). Both cocrystals exhibited an enhanced solubility and intrinsic dissolution rate (IDR) compared to Lor and adequate physical stability. The intrinsic dissolution rate of Lor-Oxa CAB is 95 times that of Lor, which makes it a promising candidate for tablet formulation development.